AMPK activation in pregnant human myometrial arteries from high-altitude and intrauterine growth-restricted pregnancies - Lorca, Ramón A. (Am J Physiol Heart Circ Physiol, 2020)
High-altitude (>2,500 m) residence increases the incidence of intrauterine growth restriction (IUGR) due, in part, to reduced uterine artery blood flow and impaired myometrial artery (MA) vasodilator response. A role for the AMP-activated protein kinase (AMPK) pathway in protecting against hypoxia-associated IUGR is suggested by genomic and transcriptomic studies in humans and functional studies in mice. AMPK is a hypoxia-sensitive metabolic sensor with vasodilatory properties. Here we hypothesized that AMPK-dependent vasodilation was increased in MAs from high versus low-altitude (<1,700 m) Colorado women with appropriate for gestational age (AGA) pregnancies and reduced in IUGR pregnancies regardless of altitude. Vasoreactivity studies showed that, in AGA pregnancies, MAs from high-altitude women were more sensitive to vasodilation by activation of AMPK with A769662 due chiefly to increased endothelial nitric oxide production, whereas MA responses to AMPK activation in the low-altitude women were endothelium independent. MAs from IUGR compared with AGA pregnancies had blunted vasodilator responses to acetylcholine at high altitude. We concluded that 1) blunted vasodilator responses in IUGR pregnancies confirm the importance of MA vasodilation for normal fetal growth and 2) the increased sensitivity to AMPK activation in AGA pregnancies at high altitude suggests that AMPK activation helped maintain MA vasodilation and fetal growth. These results highlight a novel mechanism for vasodilation of MAs under conditions of chronic hypoxia and suggest that AMPK activation could provide a therapy for increasing uteroplacental blood flow and improving fetal growth in IUGR pregnancies. NEW & NOTEWORTHY Intrauterine growth restriction (IUGR) impairs infant well- being and increases susceptibility to later-in-life diseases for mother and child. Our study reveals a novel role for AMPK in vasodilating the myometrial artery (MA) from women residing at high altitude (>2,500 m) with appropriate for gestational age pregnancies but not in IUGR pregnancies at any altitude.